Revitalizing Islamic Religious Education at the Junior Secondary Level through Meaningful Learning: A Systematic Literature Review - Hasanah, Naomi Ainun; Permana, Irfan Setia (Sinthop: Media Kajian Pendidikan, Agama, Sosial dan Budaya, 2025)
Islamic Religious Education (IRE) at the junior secondary level (SMP/MTs) continues to face challenges related to student engagement and the relevance of learning to students’ everyday experiences. Many studies indicate that IRE instruction is still dominated by conventional approaches that emphasize content delivery, leaving limited space for reflection and value internalization. In response to these challenges, meaningful learning has been discussed as an approach that connects religious knowledge with students’ lived realities. This study presents a Systematic Literature Review (SLR) guided by the PRISMA 2020 framework to examine empirical research on the implementation of meaningful learning in Islamic Religious Education at the SMP/MTs level. Articles published between 2014 and 2024 were collected from several academic databases, including Google Scholar, Springer Nature Link, JSTOR, DOAJ, Taylor & Francis, and Brill. Through a staged screening process, ten empirical studies were selected for final analysis. The findings show that meaningful learning in IRE is commonly implemented through contextual and student-centered strategies, such as Contextual Teaching and Learning, Problem-Based Learning, project-based activities, cooperative learning, and reflective practices. These approaches are associated with increased student engagement, deeper understanding of religious concepts, and stronger opportunities for value internalization. However, most studies focus on short-term outcomes and provide limited discussion of assessment and long-term impacts. This review highlights the need to position meaningful learning as a reflective and context-sensitive pedagogical approach in Islamic Religious Education.